Draft third five-year plan : large scale and medium industries - Government of India (New Delhi : Planning Commision, Government of India., 1960)
This draft outline brings together the results of studies on the Third Five Year Plan. The plan covers: social and economic growth approach; resources for the plan; policy and organisation; human resources and social service; technical manpower and scientific research; agriculture and rural economy; irrigation and power; village and small industries; transport and communications.
lje 16/10/18
Loans
Keywords: Economic plan; Economic development